Respuestas

2012-04-13T05:01:05+02:00

Primero

 

(5x-1 + 3-x ) "2 = (2x)"2                 "2-----> al cuadrado

 

5x-1+ 2(5x-1)*(3-x) + 3-x = 2x

 

215x-5x"2-3+x=-2 -2x

 

(-2-5x"2+16x-3)"2= (2x+2)"2

 

-20x"2+64x-12= 4x"2+8x+4

 

24x"2-56x+16=0

dividimos para 8

3x"2-7x+2=0

     7+ 49-24

X=__-______

           6

 

x= 7+25/6--->25=5

 

x1=7+5/6      x2=7-5/6

 

x1=12/6        x2=1/6

 

x1=2


AGRADECER NO CUESTA NADA, EPERO QUE TE HAYA SERVIDO MI RESPUESTA


2012-04-13T05:01:18+02:00

raiz cuadrada de 5x se va con raiz cuadrada de 3 y 2

 

quedaria -x=-1

 

x=1